2013
DOI: 10.2340/00015555-1677
|View full text |Cite
|
Sign up to set email alerts
|

Acne: Risk Indicator for Increased Body Mass Index and Insulin Resistance

Abstract: Acne appears to represent a visible indicator disease of over-activated mTORC1 signalling, an unfavour-able metabolic deviation on the road to serious common Western diseases of civilisation associated with increased body mass index and insulin resistance. Exaggerated mTORC1 signalling by Western diet explains the association of acne with increased body mass index, insulin resistance, and early onset of menarche. Both, a high glycaemic load and increased consumption of milk and milk products, staples of Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 67 publications
5
65
2
11
Order By: Relevance
“…In the past, nutrition was not a proven cause of acne. However, recent publications show a link between some dietary factors and acne . Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates …”
Section: Resultsmentioning
confidence: 99%
“…In the past, nutrition was not a proven cause of acne. However, recent publications show a link between some dietary factors and acne . Nowadays, main food classes considered triggering acne are dairy products (especially skim milk) and hyperglycaemic carbohydrates …”
Section: Resultsmentioning
confidence: 99%
“…2 Hyperglycaemic carbohydrates and insulinotrophic milk/dairy products have been identified to drive acne pathogenesis by promoting increased insulin/ insulin like growth factor-1 signalling. 9 A study by Tasli et al has suggested that insulin like growth factor-1 cytosine-adenine repeat (IGF-1 CA 19) polymorphism may contribute to a predisposition to acne in Turkish patients. 1 A study by Balta et al suggested that insulin resistance may not play a major role in the pathogenesis of post-adolescent acne.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acne often exhibit increased levels of serum glucose and insulin as well as insulin resistance, and its association has been long recognized [72]. Interestingly, in patients with acne vulgaris, desnutrin, also called adipose triglyceride lipase (ATGL), has been found to be low and to have a positive correlation with insulin and HOMA-IR values [73].…”
Section: Introductionmentioning
confidence: 99%